FROM OBSERVERS TO PARTICIPANTS: SINO-MUSLIM INTELLECTUAL’S ENGAGEMENT WITH THE ISLAMIC WORLD IN THE EARLY TWENTIETH CENTURY - Bao Hsiu-Ping (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
This paper aims to shed light on the evolving perception of the Sino-Muslim intellectuals on Pan Islamism as they engaged with the Islamic world. Scholarly literature examining the relationship between Sino-Muslim intellectuals and the Islamic world often discusses the role of Chinese Azharites in the 1930s. However, the engagement of Sino-Muslim intellectuals with the Islamic world prior to the emergence of Chinese Azharites is rarely explored. This paper aims to address this gap by examining the process of Sino-Muslim intellectuals’ engagement with the Islamic world in the early twentieth century, using magazines, books and travelogues published by Sino-Muslim intellectuals and official archives as primary sources. It argues that their level of engagement with the Islamic world depends on their acceptance of Pan-Islamism, an idea that emerged in the late nineteenth century advocating for the political unity of the Islamic world. Notably, the engagement of Sino-Muslim intellectuals with the Islamic world was not always as harmonious. Prior to the end of World War I, most Sino-Muslim intellectuals were sceptical of the idea of Pan-Islamism, which hindered the relationship between Sino Muslim communities and governments. Nevertheless, after World War I, thanks to the efforts of certain Sino-Muslim intellectuals, they not only embraced this idea but also actively participated in various issues in the Islamic world.